Congenital adrenal calcifications as the first clinical indication of sphingosine lyase insufficiency syndrome: A case report and review of the literature. Issue 11 (16th August 2022) - Ron, Hayley A.; Scobell, Rebecca; Strong, Amy; Salazar, Elizabeth G.; Ganetzky, Rebecca
Abstract: Sphingosine Lyase Insufficiency Syndrome (SPLIS) or SGPL1 Deficiency is a newly described entity that is characterized by steroid‐resistant nephrotic syndrome, primary adrenal insufficiency, lymphopenia, ichthyosis, and/or endocrine and neurologic abnormalities. The earliest identification of SGPL1 pathogenic variants in association with this syndrome was reported in 2017. Since then, at least 36 patients have been reported with this pediatric syndrome. Here, we report a new patient with SPLIS who had a prenatal finding of adrenal calcifications, congenital nephrotic syndrome, and abnormal newborn screening concerning for Severe Combined Immunodeficiency. We conclude that SPLIS is a clinically recognizable condition with prenatal onset. This case should increase awareness of SPLIS in the differential diagnosis for adrenal calcifications. We present a case on the severe end of the clinical spectrum of SPLIS, and a review of the literature.